2019
DOI: 10.1038/s41467-019-10563-9
|View full text |Cite|
|
Sign up to set email alerts
|

Time-restricted feeding restores muscle function in Drosophila models of obesity and circadian-rhythm disruption

Abstract: Pathological obesity can result from genetic predisposition, obesogenic diet, and circadian rhythm disruption. Obesity compromises function of muscle, which accounts for a majority of body mass. Behavioral intervention that can counteract obesity arising from genetic, diet or circadian disruption and can improve muscle function holds untapped potential to combat the obesity epidemic. Here we show that Drosophila melanogaster (fruit fly) subject to obesogenic challenges exhibits metabolic disease phenotypes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 70 publications
7
117
1
3
Order By: Relevance
“…This deviation from the classic "S-shaped" survival plot seems to be a feature of virgin Drosophila, as previous studies also reported similar survival dynamics (Markow, 2011;Villanueva et al, 2019). In flies, TRF has been shown to have beneficial effects on sleep in males ( (Gill et al, 2015), female data not shown in that study), and improve cardiac health and muscle function in both sexes (Gill et al, 2015;Villanueva et al, 2019). Previous work examining the effect of TRF on longevity in both sexes found no benefit, in contrast to the data presented here.…”
Section: Sex Differences In Trf Effectssupporting
confidence: 75%
See 1 more Smart Citation
“…This deviation from the classic "S-shaped" survival plot seems to be a feature of virgin Drosophila, as previous studies also reported similar survival dynamics (Markow, 2011;Villanueva et al, 2019). In flies, TRF has been shown to have beneficial effects on sleep in males ( (Gill et al, 2015), female data not shown in that study), and improve cardiac health and muscle function in both sexes (Gill et al, 2015;Villanueva et al, 2019). Previous work examining the effect of TRF on longevity in both sexes found no benefit, in contrast to the data presented here.…”
Section: Sex Differences In Trf Effectssupporting
confidence: 75%
“…In addition to DR including caloric restriction and restricting uptake of certain nutrients or amino acids, other dietary interventions have been shown to have positive effects on aging: intermittent fasting, which includes various protocols of feeding or eating and fasting for longer than 24h (Patterson and Sears, 2017), and time-restricted feeding (TRF), where food intake is restricted daily to certain hours of the day (Chaix et al, 2019b). In Drosophila, TRF has been shown to attenuate age-related cardiac decline during aging (Gill et al, 2015), as well as increase sleep and muscle function (Villanueva et al, 2019). In mice, TRF lowers blood cholesterol and sugar levels, reduces body weight, inflammation and dysbiosis, while increasing energy expenditure, motor control and endurance (Chaix et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…30 However, various studies show that circadian disruption, either genetic or environmental variants (ie, nocturnal light exposure, sleep disorders, social jet lag, and late-night snacking), widely affects host lipid metabolism and accelerates the development of obesity. [31][32][33][34] For example, both Clock mutant (delta 19) and Bmal1 knockout (KO) mice exhibit glucose intolerance, reduced insulin secretion, increased sensitivity to high-fat diet feeding, are hyperphagic and became overweight. [35][36][37] Additionally, glucose metabolism and systemic glucose homeostasis are also impaired in peripheral tissues-specific (skeletal muscle, beta cells and liver) Bmal1 KO models.…”
Section: Obesit Ymentioning
confidence: 99%
“…However, a 3 h or 6 h starvation during the day was not enough to extend the lifespan [65]. Additionally, TRF did not increase the median lifespan of fruit flies, although TRF improved the muscle performance and attenuated age-related cardiac dysfunction [31,68].…”
Section: Fruit Fly (Drosophila Melanogaster)mentioning
confidence: 98%
“…A relatively diverse fasting study design can be carried out in fruit flies. In the case of ADF, food is provided every two days and fasting is performed for 24 h. Recent studies have found that a 2-day fed:5-day fasted IF regime [67] and a TRF regime with daily access to food during the day and water access during the night [68] can be implemented in fruit flies. In the IF regime's case, flies were treated for IF for the first 30 days of adulthood and then switched to an ad libitum diet due to high mortality by fasting in older flies [67].…”
Section: Fruit Fly (Drosophila Melanogaster)mentioning
confidence: 99%